Status Keberlanjutan Usahatani Agroforestry Tanaman Porang pada Lembaga Masyarakat Desa Hutan Kemuning Asri di Gombengsari Kalipuro - M. Hadi Purnomo; Rizal Rizal; Sri Sundari (Kadiri University, 2022)
The concept of community-based agroforestry development is a forest development concept that is expected to meet the needs and welfare of the people living around the forest. One example of the non-timber forest resources mainly allocated to the forest community is porang (Amorphophallus oncophyllus Prain) plant. Porang is a tropical tuberous herbaceous plant producing carbohydrates, fats, proteins, minerals, vitamins, and fiber. This study was aimed to analyze the sustainability of the ecological dimensions of porang at the Forest Village Community Institution (FLCI) Kemuning Asri. The study method was the Multi-Dimensional Scaling (MDS) method to analyze sustainability. It consisted of seven attributes: soil suitability, soil pH, soil fertility, water availability (based on rainfall), shade density, land elevation, and soil temperature. The factor that significantly affected the sustainability of the ecological dimension and required consideration was the level of shade density with a value of 5.99. Porang agroforestry farming at FLCI Kemuning Asri was sustainable in terms of the ecological dimension. It is indispensable to develop porang plants to improve their sustainability.Konsep pengembangan agroforestri berbasis masyarakat merupakan konsep pengembangan hutan yang diharapkan dapat memenuhi kebutuhan dan kesejahteraan masyarakat sekitar hutan. Kemungkinan sumber daya hutan non-kayu terutama dialokasikan untuk masyarakat adalah tanaman porang. Porang adalah (Amorphophallus oncophyllus Prain) tumbuhan yang menghasilkan karbohidrat, lemak, protein, mineral, vitamin, dan serat. Penelitian ini bertujuan untuk menganalisis keberlanjutan dimensi ekologi dari agroforestri tanaman porang pada LMDH Kemuning Asri. Metodologi yang digunakan adalah Rap-LMDH melalui metode Multi Dimensional Scaling (MDS) untuk menganalisis keberlanjutan dengan 7 atribut yaitu tingkat kesesuaian tanah, tingkat PH tanah, tingkat kesuburan tanah, tingkat ketersediaan air berdasarkan curah hujan, tingkat kerapatan naungan, tingkat ketinggian lahan dan tingkat kesesuaian suhu. Faktor yang sangat mempengaruhi keberlanjutan pada dimensi ekologi dan yang perlu diperhatikan adalah tingkat kerapatan naungan dengan nilai 5,99. Usahatani agroforestri tanaman porang pada LMDH Kemuning Asri memiliki keberlanjutan ditinjau dari dimensi ekologi sehingga sangat perlu untuk dilakukan pengembangan tanaman porang untuk meningkatkan keberlanjutan.